2018
DOI: 10.1002/pssa.201800038
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Trace Elements (In, Sn) on the Hardening Process of Al–Cu Alloys

Abstract: Adding trace elements (Cd, In, Sn) to Al‐Cu‐based alloys can significantly improve their strength by the growth of small and finely distributed θ′ precipitates. However, the underlying atomic mechanisms of their nucleation are so far only superficially understood. We follow the precipitation process, that is changes in the microstructure, by different methods: differential scanning calorimetry (DSC), giving information on formation and dissolution of precipitates, 3D atom probe tomography (3DAP), giving inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The thermograms show a series of exo-and endothermic peaks representing, respectively, the formation and dissolution of different precipitate types. The precipitation sequence in Al-Cu is well known and has already been characterized by DSC in the literature (Son et al, 2005;Lotter et al, 2018). Exothermic peaks will be denoted in order of appearance by X, Y, Z, while for endothermic peaks we will use A, B, C, .…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…The thermograms show a series of exo-and endothermic peaks representing, respectively, the formation and dissolution of different precipitate types. The precipitation sequence in Al-Cu is well known and has already been characterized by DSC in the literature (Son et al, 2005;Lotter et al, 2018). Exothermic peaks will be denoted in order of appearance by X, Y, Z, while for endothermic peaks we will use A, B, C, .…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…2 show that the base alloy with 1.7 at.% Cu (red line) just exhibits the typical exo-or endothermal peaks corresponding to the formation of precipitates (clusters, GP zones and later intermetallic phases) or their dissolution (see Baur/Gerold [37] or Hardy [1] for early reviews). Please, note that this measurement of a well-known system just serves as a reference (see [38] for a thorough discussion).…”
Section: Bottom)mentioning
confidence: 99%
“…Therefore, optimising Cu content has an important influence on the age-hardening and mechanical properties. In addition, Sn is considered as an important trace element to restrain vacancy annihilation due to its high binding energy with vacancies [4][5][6]. Studies have shown that Sn promotes the formation of the θ phase by reducing the interfacial energy between the precipitate and the matrix or acting as heterogeneous nucleation particles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the effect of Sn on the precipitation kinetics. Most of the studies are based on transmission electron microscopy or 3D atom probe tomography combined with the age-hardening curve [4][5][6]. However, there are few quantitative analyses on the effect of Sn on precipitation kinetics.…”
Section: Introductionmentioning
confidence: 99%